2014
DOI: 10.1080/08957959.2014.981262
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofEscherichia coliin milk by high pressure processing at low and subzero temperatures

Abstract: Inactivation of Escherichia coli strain ATCC 25922 in frozen and unfrozen milk by high pressure processing at low or subzero temperatures was investigated. Frozen ( − 21°C) and unfrozen (3°C) milk samples were exposed to a pressure of 300 MPa for 0.5-15 min at varying temperatures between − 5°C and 5°C. Reduction in the number of E. coli in unfrozen milk was enhanced by pressure treatment at subzero temperatures, whereas no survival was detected in frozen milk samples after a 10 min pressure treatment at − 3°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…Subsequently, we introduced freezing prior to HHP treatment. Freezing combined with HHP showed to exert antimicrobial effects as shown previously (Bulut, 2014a;2014b;Su et al, 2014b). The liquid smoke enhanced the antimicrobial effects of HHP and freezing, but this additional effect was not major.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Subsequently, we introduced freezing prior to HHP treatment. Freezing combined with HHP showed to exert antimicrobial effects as shown previously (Bulut, 2014a;2014b;Su et al, 2014b). The liquid smoke enhanced the antimicrobial effects of HHP and freezing, but this additional effect was not major.…”
Section: Discussionsupporting
confidence: 69%
“…Also, sterile BHI broth containing 3.80 % (w/v) NaCl was prepared. Subsequently, all samples were heat-sealed after removing all air as described by Bulut (2014b) and finally placed individually into a second plastic bag made of polyamide/polyethylene and vacuum packed for 30 s using a Fresco 300 Packaging Machine (SousVidetools.com).…”
Section: Preparation Of Bhi Broth Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were reported previously by Su, et al (2014) who showed more than 6 log reduction in CFU•ml -1 for E. coli ATCC 25922 in frozen nutrient broth after 1 min at 350 MPa and room temperature. In previous work (Bulut, 2014b) we reported a 3.8 log reduction in CFU•ml -1 of E. coli ATCC 25922 in frozen milk after 1 min exposure to 300 MPa at…”
Section: Effect Of Pressure and Pressurization Time On Microbial Inactivationmentioning
confidence: 83%
“…The authors suggested that solid-solid phase transitions were mainly responsible for the observed drop in cell viability. Bulut (2014b) showed that a 5 min pressure treatment at 300 MPa and 0 °C resulted in 1.8 log cycles of CFU•ml -1 reduction in numbers of E. coli strain ATCC 25922 in milk. Freezing the samples at -21°C overnight prior to pressurization under the same conditions increased the log reduction to 5.2 log CFU•ml -1 .…”
Section: Introductionmentioning
confidence: 99%